2019
DOI: 10.1080/0284186x.2018.1558371
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-mediated improvement of depression in patients with gastro-esophageal junction cancer is linked to kynurenine metabolism

Abstract: Background: Exercise may improve depression in cancer patients, yet the molecular mechanism behind this protection is poorly understood. Here, we aimed to explore the link between exercise and regulation of kynurenine (Kyn) metabolism and inflammation in patients with operable gastro-esophageal junction (GEJ) cancer patients, who improved significantly in depression score with exercise training. Material and Methods: Fifty GEJ cancer patients were allocated to 12 weeks of supervised training twice weekly inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
3
31
0
1
Order By: Relevance
“…It is noteworthy that the results obtained by both methods were similar, at least when considering the direction and magnitude of changes in sweat composition. Moreover, the results obtained correspond well with data obtained by other researchers investigating changes of kynurenines in blood 6 , 34 , 40 43 , 47 . Therefore there is reason to conclude that the measurement of TRP, KYN and KYNA in sweat may have the diagnostic potential, and may also help to establish an exercise regime appropriate for the age, gender, and health status of rehabilitation participant.…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that the results obtained by both methods were similar, at least when considering the direction and magnitude of changes in sweat composition. Moreover, the results obtained correspond well with data obtained by other researchers investigating changes of kynurenines in blood 6 , 34 , 40 43 , 47 . Therefore there is reason to conclude that the measurement of TRP, KYN and KYNA in sweat may have the diagnostic potential, and may also help to establish an exercise regime appropriate for the age, gender, and health status of rehabilitation participant.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, QUINA levels were significantly elevated in the urine of breast cancer patients in comparison to healthy women (Figure 1), which likely is a direct consequence of the enhanced TRP degradation in these patients. Elevated QUINA levels and QUINA/KYNA ratios in patients may also be the consequence of an inflammation driven induction of kynurenine 3-monooxygenase (KMO) (39). Comparison of the effects of resistance exercise between breast cancer patients (IG) and healthy women (HIG) revealed that while urine QUINA levels and the QUINA/KYNA ratio were reduced in the healthy subjects (HIG), breast cancer patients (IG) showed reduced KYNA/KYN ratios and elevated QUINA/KYNA ratios after completion of the 12-week exercise training (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in mice with PGC1α being overexpressed or knocked down in muscle tissue specifically, KAT expression is increased and decreased, respectively, indicating the importance of PGC1α in KAT regulation [16]. In a recent study of cancer patients, an exercise-mediated improvement in depression was also linked to KYN metabolism [20]. We cannot rule out that other organs or tissues are involved in the elevated circulating KYN levels in COPD as well, but these findings suggest that exercise training, currently a core component of pulmonary rehabilitation to treat muscle dysfunction in COPD [21], by restoring muscle PGC1α signaling and KAT4 expression, might also be beneficial in the treatment of mental comorbidities.…”
Section: Discussionmentioning
confidence: 99%